Influence of the PBL Model on Increasing HOTS and Students' Learning Motivation in Medan High Schools - Angel S. Panjaitan; Marham Sitorus (Universitas Tadulako, 2025)
This research is motivated by the continued use of conventional learning models (e.g., lectures) in instructional practice. In the learning process, it remains more teacher-centred, with students listening and receiving the material provided. This causes a lack of critical thinking and student motivation in learning. The purpose of this study is to determine the effect of the PBL learning model on improving HOTS and student motivation, and also to determine the effectiveness of the PBL learning model in improving students' HOTS. This research is a quantitative study with a quasi-experimental method. The study results indicate a significant improvement in students' HOTS, as evidenced by the pretest and posttest scores.